2014
DOI: 10.1097/01.aud.0000436605.92129.1b
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measures of Electrode Discrimination With Electrically Evoked Auditory Change Complex and Speech-Perception Abilities in Children With Auditory Neuropathy Spectrum Disorder

Abstract: Objective: This study aimed to 1) determine the sensitivity of the electrically evoked auditory change complex (eACC) to changes in stimulating electrode position; and 2) investigate the association between results of eACC measures and behavioral electrode discrimination and their association with speech-perception performance in pediatric cochlear implant (CI) users who have auditory neuropathy spectrum disorder (ANSD). Design: Fifteen children with ANSD ranging in age between 5.4 and 18.6 yrs participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 45 publications
4
33
0
Order By: Relevance
“…The second is the spatial auditory change complex (ACC) -this is a cortical potential in response to a change in stimulating electrode during a continuous stimulus. Whilst both the spatial ACC and the MMN have been used to measure electrode discrimination (Brown et al, 2008;He et al, 2014;Wable et al, 2000), there is evidence to suggest that the ACC is a more sensitive marker of peripheral discrimination (Martin and Boothroyd, 1999).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The second is the spatial auditory change complex (ACC) -this is a cortical potential in response to a change in stimulating electrode during a continuous stimulus. Whilst both the spatial ACC and the MMN have been used to measure electrode discrimination (Brown et al, 2008;He et al, 2014;Wable et al, 2000), there is evidence to suggest that the ACC is a more sensitive marker of peripheral discrimination (Martin and Boothroyd, 1999).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…It may be that the spatial ACC is a more strongly correlated with speech perception in experienced CI users in whom the the full potential for discrimination has been achieved. Indeed, He et al (2014) found that the EDL measured around a mid-array electrode with the spatial ACC was associated with speech perception when categorized as 'good' or 'poor'. Of note, most of the participants in their study had several years of CI experience.…”
Section: Electrode Discrimination and Speech Perceptionmentioning
confidence: 99%
“…Despite an absent or abnormal ABR, the auditory event-related potentials (ERPs), including the onset response and the auditory change complex (ACC), can often be recorded from patients with ANSD (Demitrijevic et al, 2011; Kraus et al, 2000; He et al, 2013a, 2013b; Michalewski et al, 2005, 2009; Narne & Vanaja, 2008; Pearce et al, 2007; Rance et al, 2002; Sharma et al, 2011; Starr et al, 1996). These two responses are cortically generated potentials that can be recorded from surface electrodes placed on the scalp.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the PBK word scores are correlated with the behavioral electrode-discrimination thresholds (r = -0.96), with good performers having significantly larger EACC than poor performers (p < 0.05). While these two studies (He et al, 2014) showed a broad range of variance in response morphologies of EACC in CI children with ANSD, authors did not discuss the changes in the EACC with age in this population. Martinez et al (2013) recorded ACCs in children with NH (n=5) and bilateral SNHL (n=5) aged from 2 to 6 years.…”
Section: Accs In Ha and CI Usersmentioning
confidence: 93%
“…In the following study, He et al (2014) measured EACC in 15 CI children (between 5 and 17 years at the time of testing) who were diagnosed with ANSD, using the same method and stimuli. This time they presented the same biphasic pulses presented to the electrode 12 for 400 mses but then changed the second electrode, varying from electrode 13 to electrode 22.…”
Section: Accs In Ha and CI Usersmentioning
confidence: 99%